2009
DOI: 10.1179/136217109x437178
|View full text |Cite
|
Sign up to set email alerts
|

Stainless steel weld metal designed to mitigate residual stresses

Abstract: There have been considerable efforts to create welding consumables which on solid state phase transformation partly compensate for the stresses which develop when a constrained weld cools to ambient temperatures. All of these efforts have focused on structural steels which are ferritic. In the present work, alloy design methods have been used to create a stainless steel welding consumable which solidifies as d ferrite, transforms almost entirely into austenite which then undergoes martensitic transformation at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
55
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(57 citation statements)
references
References 44 publications
1
55
0
1
Order By: Relevance
“…It is generally taken that the transformation should occur at a temperature low enough to preclude subsequent build-up of stress, but should be complete by the time the metal cools to room temperature 10 [154,155]. Figure 16 shows schematically the effect of different phase transformations on the build-up of stress in uniaxially-constrained steel specimens as they are cooled from 1000°C.…”
Section: Weld Materials Transformationsmentioning
confidence: 99%
“…It is generally taken that the transformation should occur at a temperature low enough to preclude subsequent build-up of stress, but should be complete by the time the metal cools to room temperature 10 [154,155]. Figure 16 shows schematically the effect of different phase transformations on the build-up of stress in uniaxially-constrained steel specimens as they are cooled from 1000°C.…”
Section: Weld Materials Transformationsmentioning
confidence: 99%
“…The stress may therefore favour the formation of certain crystallographic variants of the martensite over others whose deformations do not comply with the applied stress. [5] In recent years, this phenomenon of transformation plasticity has been exploited for one of the most pernicious problems in welding technology, that of the residual stresses [51][52][53][54][55][56][57][58][59][60][61][62][63][64][65]. The aim is to design welding alloys which compensate for the effects of thermal contraction and stress whilst maintaining the overall mechanical performance [66,67].…”
Section: Martensite and Bainite As Plastic Deformationsmentioning
confidence: 99%
“…• C. This has led to welding consumables which not only have been demonstrated to reduce residual stress and distortion, but also to consequently enhance the fatigue life by impressive amounts [51][52][53][54][55][56][57][58][59][60][61][62][63][64][65]. This is an excellent example of how phase transformation theory has contributed to the alloy design for an essentially practical purpose.…”
Section: Martensite and Bainite As Plastic Deformationsmentioning
confidence: 99%
“…[3][4][5][6][7][8][9] It has been shown that weld fabrication using, for example, filler metal wires with a lowered  transformation temperature (so-called low transformation temperature or LTT wires) can result in lowered residual stresses and distortion. 8,[10][11][12] Text Click here to download Manuscript: Beres_Text. docx 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 2 Where the transformation is entirely reconstructive, one might initially believe that the transformation strain will simply be due to the volume change between the two unit cells.…”
Section: Introductionmentioning
confidence: 99%